Tantangan Penerapan Pendidikan Islam Pada Generasi Z - Rodia Tammardiah Hasibuan; Iza Faridatul Amalia; Daman Daman; Sasmiyarti Sasmiyarti; Asmaul Husna; Hendrizal Hendrizal (Departement of Mathematics Education, 2024)
Islamic education for Generation Z faces unique and complex challenges. Generation Z, born in the digital era, faces challenges in maintaining religious values ​​while remaining engaged in the ever-expanding digital world. These challenges include isolation from religious communities, lack of time for worship, academic and social stress, and lack of time for religious learning. In this context, Islamic education must respect and accommodate the diverse backgrounds and preferences of students. Islamic Education teachers and instructors need to understand the social, cultural, and technological contexts faced by Generation Z and be able to relate Islamic teachings to the daily lives and situations faced by students. In addition, Islamic education must also focus on building students' character with strong moral and ethical religious values. With a wise approach and strong support, Generation Z can live a balanced and meaningful life in the light of Islamic teachings.